Financial Linkages Between the U.S. and Latin America : Evidence from Daily Data - Ganguly, Srideep; Benelli, Roberto (Washington, D.C. : International Monetary Fund, 2007)
Motivated by recent bursts of global financial market turbulence, this paper investigates the linkages between the financial markets in the United States and those of the seven largest Latin American economies, focusing on the impact of shocks originating in the U.S. stock, bond, and currency markets. After documenting that cross-country linkages were different in "tranquil" and "turbulent" times within our sample, we find that: (i) for stock markets, recent episodes of market turbulence stood out from preceding ones as they showed an increased sensitivity of Latin American markets to U.S. shocks, reversing a trend of weakening linkages; (ii) currency markets in Latin America exhibited a decrease in cross-market linkages with the U.S. during the last episodes of volatility, consistent with increased exchange rate flexibility in the region; and (iii) the external bond markets in Latin America remained on a trend of weakening linkages with U.S. corporate bonds, while they increased their sensitivity to movements in other emerging market bond markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet